The genus Panzeria Robineau-Desvoidy (Diptera: Tachinidae) from Japan - Shima, Hiroshi (Zootaxa, 2020)
Japanese species of Panzeria Robineau-Desvoidy in the sense of Wood and Cerretti are revised. Eighteen species are recorded from Japan, five of which are described as new and illustrated: P. atriventris sp. nov., P. bisetosa sp. nov., P. japonica sp. nov., P. meridionalis sp. nov., and P. rufitibialis sp. nov. Panzeria tuberculata (Zimin) is removed from synonymy with P. emdeni (Mesnil) and is revived as a valid species, comb. nov. Panzeria mimetes (Zimin) is removed from the Japanese fauna. The male and female terminalia of 16 species are illustrated and a key to 18 species is provided. The new name Panzeria chaoi nom. nov. is proposed for Eurythia tuberculata Chao & Shi, 1981, because P. tuberculata (Zimin) is recognized as valid.